Genetic Adaptations, Biases, and Evolutionary Analysis of Canine Distemper Virus Asia-4 Lineage in a Fatal Outbreak of Wild-Caught Civets in Thailand - Piewbang, Chutchai (Viruses, 2020)
Canine morbillivirus (CDV) is a serious pathogen that can cause fatal systemic disease in a wide range of domestic and wildlife carnivores. Outbreaks of CDV in wildlife species lead to questions regarding the dispersal of the CDV origin. In the present study, we identified a fatal CDV outbreak in caged wild-caught civets in Thailand. Full-length genetic analysis revealed that CDV from the Asia-4 lineage served as the likely causative agent, which was supported by the viral localization in tissues. Evolutionary analysis based on the CDV hemagglutinin (H) gene revealed that the present civet CDV has co-evolved with CDV strains in dogs in Thailand since about 2014. The codon usage pattern of the CDV H gene revealed that the CDV genome has a selective bias of an A/U-ended codon preference. Furthermore, the codon usage pattern of the CDV Asia-4 strain from potential hosts revealed that the usage pattern was related more to the codon usage of civets than of dogs. This finding may indicate the possibility that the discovered CDV had initially adapted its virulence to infect civets. Therefore, the CDV Asia-4 strain might pose a potential risk to civets. Further epidemiological, evolutionary, and codon usage pattern analyses of other CDV-susceptible hosts are required.